The impact of water level fluctuations on a delayed prey–predator model. (February 2015) - Moussaoui, Ali; Bassaid, Siham; Ait Dads, EL Hadi
Abstract: Prey–predator interactions are influenced by many ecological factors. In this paper, a delayed periodic prey–predator model with instantaneous negative feedback is investigated to study the impact of water level on persistence of two fish populations living in an artificial lake. By using the continuation theorem of coincidence degree theory, and by constructing suitable Lyapunov functionals, a set of easily verifiable sufficient conditions is derived for the existence, uniqueness and global stability of positive periodic solutions to the model. Numerical simulation is carried out to illustrate the feasibility of our main results.